Study on the mechanical characteristics of Xia-Ang in the Song-style Dou-Gong set on columns. (July 2022) - Zhang, Long; Dong, Weikun; Zhou, Ting
Abstract: As an important node in ancient wooden buildings, Dou-Gong serves functions such as energy dissipation and overhanging eaves. Xia-Ang plays an important cantilever role in Dou-Gong. To study the mechanical characteristics of Xia-Ang, we conducted horizontal quasi-static experiments and finite element numerical simulations to investigate two typical Song-style Dou-Gong sets on columns. The difference between the two types of Dou-Gongs is the presence of Xia-Ang components. The results of mechanical experiments showed that the hysteretic curves of the two types of Dou-Gong were in reverse "s" shape under the force from the beam direction, which has obvious pinch characteristics, and the Dou-Gong components were cracked to a certain extent. Under the force from the direction of the Fang, the hysteretic curve was complete, and no obvious splitting or warping components were found in the Dou-Gong. The influence of Xia-Ang on the mechanical characteristics of Dou-Gong was mainly reflected along the beam direction, but had no effect on the Fang direction. When the Dou-Gong was pushed by the beam, the horizontal stiffness of the Dou-Gong was strengthened by Xia-Ang, and the horizontal stiffness of the Dou-Gong with Xia-Ang was increased by 29.41% compared with that of the Dou-Gong without Xia-Ang. When the Dou-Gong was under tension, Xia-Ang weakened the horizontal stiffness by 23.75%. Two types of Dou-Gong were studied using the ABAQUS finite element method. The finite element model was verified and revised by comparing the simulation and experimental results. The numerical simulation results showed that when the beam was loaded, the horizontal stiffness of the Dou-Gong increased by 28.15% owing to the presence of Xia-Ang under the action of thrust. Under tensile force, the horizontal stiffness of Dou-Gong decreased by 24.26%.